2019
DOI: 10.1007/s11912-019-0769-3
|View full text |Cite
|
Sign up to set email alerts
|

CDK 4/6 Inhibitors in Breast Cancer: Current Controversies and Future Directions

Abstract: Purpose of Review: To describe the clinical role of CDK 4/6 inhibitors in hormone receptor-positive (HR+) metastatic breast cancer (HR+ MBC) as well as current controversies and evolving areas of research. Recent Findings: Palbociclib, ribociclib, and abemaciclib are each approved in combination with an aromatase inhibitor or fulvestrant for HR+ MBC. Abemaciclib is also approved as monotherapy for pre-treated patients. Key questions in the field include whether all patients with HR+ MBC should receive a CDK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
142
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 141 publications
(147 citation statements)
references
References 45 publications
(51 reference statements)
2
142
0
3
Order By: Relevance
“…[7][8][9][10][11] Although tremendous efforts have been made to nd new CDK4/6i, 12,13 the current array of inhibitors failed to discriminate between both homologues. 14,15 The majority of strategies to design CDK4/6i were focused on CDK4/6cyclin D dimer activities without considering CDK interacting protein/kinase inhibitory protein (CIP/KIP) family proteins. 16 Very recently, crystallographic studies demonstrated that p21 CIP and p27 KIP are assembly factors for active CDK4/6-cyclin D trimer complexes which are not sensitive to CDK4/6i.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] Although tremendous efforts have been made to nd new CDK4/6i, 12,13 the current array of inhibitors failed to discriminate between both homologues. 14,15 The majority of strategies to design CDK4/6i were focused on CDK4/6cyclin D dimer activities without considering CDK interacting protein/kinase inhibitory protein (CIP/KIP) family proteins. 16 Very recently, crystallographic studies demonstrated that p21 CIP and p27 KIP are assembly factors for active CDK4/6-cyclin D trimer complexes which are not sensitive to CDK4/6i.…”
Section: Introductionmentioning
confidence: 99%
“…The cyclin-dependent kinase 4/6 inhibitors (CDK4/6i) have entered widespread use in both the first- and subsequent-line setting for patients with hormone-receptor positive (HR+), human epidermal growth factor receptor 2 negative (HER2-) metastatic breast cancer (MBC). 1, 2 Their application has resulted in significant improvements in progression-free survival (PFS) and overall survival (OS) for treatment-naïve and previously treated patients in combination with anti-estrogens. 3–9 Abemaciclib has shown efficacy as a single agent in endocrine-refractory disease, and has been approved for use as monotherapy in pre-treated patients with HR+/HER2-MBC.…”
Section: Introductionmentioning
confidence: 99%
“…The PALOMA-3 trial (fulvestrant with palbociclib/placebo) included women with HR+/HER2-MBC, ones who were pre-menopausal (goserelin was added for these women) or post-menopausal and who had relapsed or progressed during prior endocrine treatment (78% of the entire population). In this trial, there was no limit to previous endocrine therapies (2nd line or more) 25,26 and 34% of the patients had received prior chemotherapy for ABC. The addition of palbociclib resulted in an improvement in PFS from 4.6 months to 11.2 months (HR 0.50; p < 0.0001).…”
Section: Cdk 4/6 Inhibitors Plus Fulvestrant: Different Populationsmentioning
confidence: 99%